2006
DOI: 10.1177/230949900601400214
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of the Hand following Flexor Tendon Repair at the ‘No Man's Land’

Abstract: The surgical method and rehabilitation protocol used for zone-2 flexor tendon injury is safe and results in a reasonably good functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 10 publications
4
17
0
1
Order By: Relevance
“…22 The recovery rate was reported as 78% in another study in patients with zone II flexor tendon injuries. 23 The only similarity between these studies and our results was the recovery rate of zone II flexor tendon injuries (70.7% in our zone II patients). The correlation between grip strength and Quick Dash scores exhibited in our study underlines the importance of grip strength in the functional evaluation.…”
Section: Discussionsupporting
confidence: 84%
“…22 The recovery rate was reported as 78% in another study in patients with zone II flexor tendon injuries. 23 The only similarity between these studies and our results was the recovery rate of zone II flexor tendon injuries (70.7% in our zone II patients). The correlation between grip strength and Quick Dash scores exhibited in our study underlines the importance of grip strength in the functional evaluation.…”
Section: Discussionsupporting
confidence: 84%
“…We found in these studies changing ratios about 67%Á94% have reported grip strength results as being good [12,13,21]. Our hand grip results were better in the Washington group (89%) than in the other group (81%).…”
Section: Discussionmentioning
confidence: 41%
“…TAM is one of the most popular systems of angular measurement [21]. We graded our results using the same criteria as Cetin et al [7], Bainbridge et al [8], and Chan et al [13], so it is possible to compare our results with theirs.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations